2012
DOI: 10.1002/adfm.201200299
|View full text |Cite
|
Sign up to set email alerts
|

A New View of Microcrystalline Silicon: The Role of Plasma Processing in Achieving a Dense and Stable Absorber Material for Photovoltaic Applications

Abstract: To further lower production costs and increase conversion efficiency of thin‐film silicon solar modules, challenges are the deposition of high‐quality microcrystalline silicon (μc‐Si:H) at an increased rate and on textured substrates that guarantee efficient light trapping. A qualitative model that explains how plasma processes act on the properties of μc‐Si:H and on the related solar cell performance is presented, evidencing the growth of two different material phases. The first phase, which gives signature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 37 publications
2
67
0
Order By: Relevance
“…Since the growth of both μc-SiO:H and pm-Si:H requires a hydrogen rich plasma, an a-SiC:H p-layer was used in the case of Table 1, which did show a strong dependence on the TCO and p-layer type, thus suggesting that the surface roughness as well as the TCO/p-layer and p/i interface regions play very important roles in determining the overall cell performance. Similar results have been reported for μc-Si:H p-i-n devices and it was also demonstrated that the FTPS method is sensitive to bulk material properties but not to local shunts induced by TCO morphology [28].…”
Section: Resultssupporting
confidence: 87%
“…Since the growth of both μc-SiO:H and pm-Si:H requires a hydrogen rich plasma, an a-SiC:H p-layer was used in the case of Table 1, which did show a strong dependence on the TCO and p-layer type, thus suggesting that the surface roughness as well as the TCO/p-layer and p/i interface regions play very important roles in determining the overall cell performance. Similar results have been reported for μc-Si:H p-i-n devices and it was also demonstrated that the FTPS method is sensitive to bulk material properties but not to local shunts induced by TCO morphology [28].…”
Section: Resultssupporting
confidence: 87%
“…18 Small amounts of carbon dioxide (CO 2 ) were added to the precursor gases of the n-and p-doped layers to incorporate oxygen during layer growth. These silicon oxide (SiO x ) doped layers are known to have two predominant effects in p-i-n solar cells: first, the incorporation of these layers leads to cells with V oc and FF values that are more tolerant to rough substrates and, second, these layers are more transparent than standard doped layers and therefore lead to less parasitic absorption.…”
Section: Single-junction Solar Cellsmentioning
confidence: 99%
“…24,25 An extended study of the material quality as a function of the growth conditions and oxygen content of the doped layers of p-i-n solar cells can be found in Ref. 18. The front contact was a 2.5-lm-thick borondoped LP-CVD ZnO layer.…”
Section: Single-junction Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations